2014
DOI: 10.1038/srep05578
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence detection of cellular nucleotide excision repair of damaged DNA

Abstract: To maintain genetic integrity, ultraviolet light-induced photoproducts in DNA must be removed by the nucleotide excision repair (NER) pathway, which is initiated by damage recognition and dual incisions of the lesion-containing strand. We intended to detect the dual-incision step of cellular NER, by using a fluorescent probe. A 140-base pair linear duplex containing the (6–4) photoproduct and a fluorophore–quencher pair was prepared first. However, this type of DNA was found to be degraded rapidly by nucleases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…At the beginning of this study, we planned to either incorporate a ribonucleotide 11 , 12 into the mismatch-containing primer used for the preparation of the double-stranded plasmid from the single-stranded DNA, or introduce a nick into the plasmid with a nicking endonuclease 28 . However, we previously found that the plasmids were degraded in the cells within several hours during the culture at 37 °C 23 . Therefore, we decided to test the plasmids without the nick, and expected that a nick would be produced non-specifically in the cells.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…At the beginning of this study, we planned to either incorporate a ribonucleotide 11 , 12 into the mismatch-containing primer used for the preparation of the double-stranded plasmid from the single-stranded DNA, or introduce a nick into the plasmid with a nicking endonuclease 28 . However, we previously found that the plasmids were degraded in the cells within several hours during the culture at 37 °C 23 . Therefore, we decided to test the plasmids without the nick, and expected that a nick would be produced non-specifically in the cells.…”
Section: Resultsmentioning
confidence: 97%
“…Judging by the results obtained in this study, neither of these two points needed to be considered. It was assumed that the nick was produced by a cellular nuclease, as expected from our previous study 23 , and the replication was avoided by using the pBlueScript vector, which lacks the eukaryotic replication origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial differences in activity of the involved DNA-repair pathway, i.e. nucleotide excision repair, can be ruled out as both RPTEC/TERT1 (Simon-Friedt et al, 2015) as well as HEK293 (Atanassov et al, 2004, Toga et al, 2014 are NER competent.…”
Section: Discussionmentioning
confidence: 99%